ANALISIS PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN DENGAN KNOWLEDGE MANAGEMENT SEBAGAI VARIABEL INTERVENING PADA TELKOM CORPORATE UNIVERSITY CENTER - Nadiya Azzah Salsabilla; Syarifuddin Syarifuddin (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to meet the needs of companies in facing industrial developments to create good resources by developing knowledge management and job training. This research also aims to improve employee performance so that they can compete in the market in order to achieve competitive advantage. This research analyzes the effect of training on employee performance with knowledge management as an intervening variable at the Telkom Corporate University Center. This research used quantitative methods with descriptive data analysis techniques and took a sample of 60 respondents from all Telkom Corporate University Center employees. This research uses proportional random sampling with the Partial Least Square-Structural Equati Modeling (PLS-SEM) program. The results of this research are descriptive analysis which shows that the training, knowledge management and employee performance variables are in the very good category. There is a positive and significant influence between training and employee performance, training and knowledge management, employee performance and knowledge management and knowledge management can mediate the relationship between training and employee performance at the Telkom Corporate University Center.